2022
DOI: 10.1186/s12891-022-05309-6
|View full text |Cite
|
Sign up to set email alerts
|

Using radiomic features of lumbar spine CT images to differentiate osteoporosis from normal bone density

Abstract: Objective This study aimed to develop a predictive model to detect osteoporosis using radiomic features from lumbar spine computed tomography (CT) images. Methods A total of 133 patients were included in this retrospective study, 41 men and 92 women, with a mean age of 65.45 ± 9.82 years (range: 31–94 years); 53 had normal bone mineral density, 32 osteopenia, and 48 osteoporosis. For each patient, the L1–L4 vertebrae on the CT images were automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A comparative experiment was performed with the following models: eXtreme gradient boosting (XGBoost) model, 18 random forest (RF) model, 19 support vector machines (SVM) model, 20 logistic regression (LR) model, 21 and backpropagation neural network (BPNN) model. 22 In addition, each machine learning algorithm solve the problems in a slightly different way, and different algorithms may give different answers to the same problem, therefore, we adopted ensemble model by weighted voting (an ensemble of XGBoost, RF, SVM, and LR models), 23 and the highest probability among the four model predictions was defined as the final prediction result.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative experiment was performed with the following models: eXtreme gradient boosting (XGBoost) model, 18 random forest (RF) model, 19 support vector machines (SVM) model, 20 logistic regression (LR) model, 21 and backpropagation neural network (BPNN) model. 22 In addition, each machine learning algorithm solve the problems in a slightly different way, and different algorithms may give different answers to the same problem, therefore, we adopted ensemble model by weighted voting (an ensemble of XGBoost, RF, SVM, and LR models), 23 and the highest probability among the four model predictions was defined as the final prediction result.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, features include both first-order features and grayscale features. Wavelet features could reflect the spatial heterogeneity of vertebral body synthetically cause they contain high-order image [36]. Studies have shown that both skewness and glrlm can reflect the heterogeneity of regions of interest [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…This study utilizes deep learning networks to predict the risk of spinal fractures based on clinical features and image data. Xue et al 17 constructed three models to predict osteoporosis through segmentation and recognition of lumbar CT images. However, the CT images selected in these studies come from a mixed population of young and elderly people, and the extracted features are not representative enough.…”
Section: Introductionmentioning
confidence: 99%
“…16 This study utilizes deep learning networks to predict the risk of spinal fractures based on clinical features and image data. Xue et al 17 generation of vertebral osteophytes in elderly people is more severe, with different texture and filtering features. [16][17][18] Therefore, this study extracts the radiological characteristics of CT images of the elderly to evaluate the efficacy of the radiological model in the diagnosis of osteoporosis.…”
mentioning
confidence: 99%